The Implementation Of A Wordwall-Based Game-Based Learning Model To Enhance Students’ Learning Interest In Islamic Religious Education At SMP Al Bukhori Kesilir - Farikhatuz Zahro; Nur Wahidah (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to describe how the Wordwall-based Game Based Learning model is implemented in Islamic Religious Education subjects and its influence on students' learning interest at SMP Al Bukhori Kesilir. A qualitative approach was applied using a case study design. Data were gathered through observation, interviews, and documentation, then processed through data reduction, data presentation, and conclusion drawing, with data validity tested using triangulation. The results show that the implementation of the Wordwall-based Game Based Learning model is carried out through three main phases: planning, implementation, and evaluation. The application of this model demonstrates a positive contribution to increasing students' learning interest, as evidenced by active involvement, sustained attention, and high enthusiasm during the learning process. This success is supported by students' learning motivation, teacher readiness, and adequate facilities and infrastructure. In addition, this study notes several constraints, namely unstable internet connection, limited learning time allocation, and the heterogeneity of students' abilities in understanding the material.